2020
DOI: 10.1093/sleep/zsaa056.444
|View full text |Cite
|
Sign up to set email alerts
|

0447 ResTNet: A Robust End-to-End Deep Learning Approach to Sleep Staging of Self Applied Somnography Studies

Abstract: Introduction Sleep stage classifications are of central importance when diagnosing various sleep-related diseases. Performing a full PSG recording can be time-consuming and expensive, and often requires an overnight stay at a sleep clinic. Furthermore, the manual sleep staging process is tedious and subject to scorer variability. Here we present an end-to-end deep learning approach to robustly classify sleep stages from Self Applied Somnography (SAS) studies with frontal EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Apart from the detected differences, the overall technical feasibility and morphology of the SAS EEG and EOG signals were on a good level and could be suitable for sleep staging of home PSGs. The findings from previous studies support that, too (Jónsson et al, 2020; Kainulainen et al, 2021; Punjabi et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Apart from the detected differences, the overall technical feasibility and morphology of the SAS EEG and EOG signals were on a good level and could be suitable for sleep staging of home PSGs. The findings from previous studies support that, too (Jónsson et al, 2020; Kainulainen et al, 2021; Punjabi et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…As a result, self‐applied EEG electrode sets and devices intended for home sleep monitoring have been introduced (Arnal et al, 2020; Carneiro et al, 2020; Kainulainen et al, 2021; Miettinen, Myllymaa, Muraja‐Murro, et al, 2018; Rusanen et al, 2021). These self‐applied EEG setups have already shown promising results in increasing the accuracy of sleep staging in HSAT to a nearly comparable level with standard PSG (Jónsson et al, 2020; Kalevo et al, 2022; Leino et al, 2022; Levendowski et al, 2017; Rusanen et al, 2023). However, self‐applied EEG is not used clinically and needs more rigorous validation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Code used for data analysis can be found at https://github.com/hubertjb/dynamic-spatial-filtering 4. A recent study reported training a neural network on artificially-corrupted sleep EEG data, with a goal similar to ours[71]; however, this study only appears as a Supplement with little information on the methods and results.…”
mentioning
confidence: 99%